A Method for Solving Percolation Overflow Boundary Based on Maximum of Horizontal Energy Loss Rate - Li, Yuandong; Hao, Bing; Li, Xiaojun; Jin, Liguo; Dong, Qing; Zhou, Zhenghua (Frontiers in Earth Science, 2021)
The determination of overflow boundary is a prerequisite for the accurate solution of the seepage field by the finite element method. In this paper, a method for solving overflow boundary according to the maximum value of horizontal energy loss rate is proposed which based on the analysis of the physical meaning of functional and the water head distribution of seepage field under different overflow boundaries, this method considers that the overflow boundary which makes the horizontal energy loss rate reaches the maximum value is the real boundary overflow. Compared with the previous iterative computation method of overflow point and free surface, the method of solving overflow boundary based on the maximum horizontal energy loss rate does not need iteration, so that the problem of non-convergence does not exist. The relative error of the overflow points is only 1.54% and 0.98% by calculating the two-dimensional model of the glycerol test and the three-dimensional model of the electric stimulation test. Compared with the overflow boundary calculated by the node virtual flow method, improved cut-off negative pressure method, initial flow method, and improved discarding element method, this method has higher accuracy.